2011
DOI: 10.1074/jbc.m110.207126
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Inhibition of Bacillus anthracis Sporulation by a Novel Class of Non-heme Globin Sensor Domains

Abstract: Pathogenesis by Bacillus anthracis requires coordination between two distinct activities: plasmid-encoded virulence factor expression (which protects vegetative cells from immune surveillance during outgrowth and replication) and chromosomally encoded sporulation (required only during the final stages of infection). Sporulation is regulated by at least five sensor histidine kinases that are activated in response to various environmental cues. One of these kinases, BA2291, harbors a sensor domain that has ϳ35% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Our transcriptional profiling studies reported previously ( Bourgogne et al, 2003 ) revealed that a pXO2 gene, pXO2-0075 , is positively regulated 54-fold by atxA . The predicted amino acid sequence of pX02-0075 exhibits high sequence similarity to the signal sensor domain of the BA2291 sporulation sensor histidine kinase, which is a key component of the sporulation phosphorelay ( White et al, 2006 ; Scaramozzino et al, 2009 ; Stranzl et al, 2011 ). White et al (2006) showed that over-expression of pXO2-0075 in a Sterne-like strain resulted in a marked decrease in sporulation that was suppressed by deletion of the sensor histidine kinase BA2291.…”
Section: Resultsmentioning
confidence: 99%
“…Our transcriptional profiling studies reported previously ( Bourgogne et al, 2003 ) revealed that a pXO2 gene, pXO2-0075 , is positively regulated 54-fold by atxA . The predicted amino acid sequence of pX02-0075 exhibits high sequence similarity to the signal sensor domain of the BA2291 sporulation sensor histidine kinase, which is a key component of the sporulation phosphorelay ( White et al, 2006 ; Scaramozzino et al, 2009 ; Stranzl et al, 2011 ). White et al (2006) showed that over-expression of pXO2-0075 in a Sterne-like strain resulted in a marked decrease in sporulation that was suppressed by deletion of the sensor histidine kinase BA2291.…”
Section: Resultsmentioning
confidence: 99%
“…However, the question of whether the nonheme globin domain of RsbRA is a sensor of acute environmental stress is unresolved. Characterization of two similar nonheme globin domains that modulate sporulation in Bacillus anthracis suggests that they are capable of sensing fatty acids and chloride via binding within a distinctive tunnel and chamber (41). The lack of these structural features seems to preclude the B. subtilis domain from sensing similar signals, and the cellular parameter to which it responds remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Globin sensor domains that lack heme binding are known, although their functions have not been determined (45,46). However, given the accumulating information about the O 2 -mediated catalytic regulation and physicochemical properties of GCSs, it is worth summarizing specific characteristics of GCSs in comparison with those of non-GCS heme-based oxygen sensors.…”
Section: Specific Characteristics Of Gcssmentioning
confidence: 99%